First evidence of gonadal hybrid dysgenesis in Chagas disease vectors (Hemiptera, Triatominae): gonad atrophy prevents events of interspecific gene flow and introgression - Azevedo, Luísa Martins Sensato [UNESP]; Cesaretto, Natália Regina [UNESP]; de Oliveira, Jader; Ravazi, Amanda [UNESP]; dos Reis, Yago Visinho [UNESP]; Tadini, Samanta Cristina Antoniassi Fernandes [UNESP]; da Silva Masarin, Isabella [UNESP]; Borsatto, Kelly Cristine [UNESP]; Galvão, Cleber; da Rosa, João Aristeu [UNESP]; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (Springer Nature, 2023)
Background: Hybridization events between Triatoma spp. have been observed under both natural and laboratory conditions. The ability to produce hybrids can influence different aspects of the parent species, and may even result in events of introgression, speciation and extinction. Hybrid sterility is caused by unviable gametes (due to errors in chromosomal pairing [meiosis]) or by gonadal dysgenesis (GD). All of the triatomine hybrids analyzed so far have not presented GD. We describe here for the first time GD events in triatomine hybrids and highlight these taxonomic and evolutionary implications of these events. Methods: Reciprocal experimental crosses were performed between Triatoma longipennis and Triatoma mopan. Intercrosses were also performed between the hybrids, and backcrosses were performed between the hybrids and the parent species. In addition, morphological and cytological analyzes were performed on the atrophied gonads of the hybrids. Results: Hybrids were obtained only for the crosses T. mopan♀ × T. longipennis♂. Intercrosses and backcrosses did not result in offspring. Morphological analyses of the male gonads of the hybrids confirmed that the phenomenon that resulted in sterility of the hybrid was bilateral GD (the gonads of the hybrids were completely atrophied). Cytological analyses of the testes of the hybrids also confirmed GD, with no germ cells observed (only somatic cells, which make up the peritoneal sheath). Conclusions: The observations made during this study allowed us to characterize, for the first time, GD in triatomines and demonstrated that gametogenesis does not occur in atrophied gonads. The characterization of GD in male hybrids resulting from the crossing of T. mopan♀ × T. longipennis♂ highlights the importance of evaluating both the morphology and the cytology of the gonads to confirm which event resulted in the sterility of the hybrid: GD (which results in no gamete production) or meiotic errors (which results in non-viable gametes). Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Experimental crosses; Hybrid sterility; Prezygotic barriers; Triatomines